Synthesis, Spectroscopic Characterization, Structural Analysis, and Evaluation of Anti-Tumor, Antimicrobial, and Antibiofilm Activities of Halogenoaminopyrazoles Derivatives - Christina Zalaru; Florea Dumitrascu; Constantin Draghici; Marilena Ferbinteanu; Isabela Tarcomnicu; Maria Marinescu; Zenovia Moldovan; George Mihai Nitulescu; Rodica Tatia; Marcela Popa (Antibiotics)
New haloaminopyrazole derivatives differing in the number of pyrazole nuclei 4a–f and 5a–e, respectively, were synthesized and characterized by 1H-NMR, 13C-NMR, IR, UV-Vis, and elemental analysis. The single-crystal X-ray diffraction method was used to describe compounds 4a and 5d. When tested on normal NCTC fibroblasts in vitro, the newly synthesized derivatives were shown to be non-cytotoxic at a dosage of 25 μg/mL. Two compounds 4a and 5d showed a high degree of biocompatibility. From the two series of compounds tested on HEp-2 human cervical carcinoma cells, compound 5d showed a more pronounced antiproliferative effect. Gram-positive strains of Staphylococcus aureus ATCC25923, Enterococcus faecalis ATCC29212, Gram-negative strains of Pseudomonas aeruginosa ATCC27853, and strains of Escherichia coli ATCC25922 were used to test the newly synthesized compounds antibacterial and antibiofilm properties. Among the studied pyrazole compounds, 2 compounds 4a and 5a with fluorine content on the phenyl ring and 4 compounds 4b, 4e, 4f, and 5b with chlorine content on the phenyl ring were noted, which proved to be the most active compared with the two reference drugs, metronidazole and nitrofurantoin. The six compounds showed a broad spectrum of action against all four tested bacterial strains, the most active being compound 4b, with a chlorine atom in the “4” position of the phenyl nucleus and a MIC of 460 μg/mL. Compounds 4a and 5a showed the best antibiofilm activity against the bacterial strain Staphylococcus aureus ATCC25923, with an MBIC of 230 μg/mL.